The Effect of Watermelon Juice Consumption on Reducing Blood Pressure in The Elderly - Gaol, Armando Marbun Lumban; Sulastri, Diah; Maryuni, Sri (Java Nursing Journal, 2025)
Background: Hypertension remains a leading global health concern, particularly among the elderly, and is a key risk factor for cardiovascular complications. In addition to pharmacological interventions, non-pharmacological therapies such as herbal remedies are gaining interest. Watermelon (Citrullus lanatus) contains bioactive compounds, including citrulline, potassium, and lycopene, that may contribute to blood pressure regulation. Purpose: This study aimed to investigate the effect of watermelon juice consumption on reducing blood pressure among elderly individuals with hypertension at the Gedong Air Health Center, Bandar Lampung, in 2025. Methods: A quasi-experimental study with a one-group pretest-posttest design was conducted involving 20 elderly respondents selected through random sampling. Participants consumed watermelon juice over a 7-day intervention period. Blood pressure measurements were taken before and after the intervention. Due to non-normal data distribution (Shapiro-Wilk p < 0.05), the Wilcoxon signed-rank test was used for analysis. Results: Pre-intervention mean systolic and diastolic blood pressure were 168.00 mmHg and 99.40 mmHg, respectively. Post-intervention means decreased significantly to 135.05 mmHg and 85.50 mmHg. The Wilcoxon test revealed a statistically significant reduction in both systolic (Z = -3.929, p = 0.001) and diastolic (Z = -3.746, p = 0.001) pressures, indicating that watermelon juice effectively reduced blood pressure levels in the elderly sample. Conclusion: Watermelon juice demonstrated a significant antihypertensive effect in elderly individuals, suggesting its potential as a complementary non-pharmacological approach in managing hypertension. Further studies with larger samples and control groups are warranted